Lévi-Strauss et l’Asie. L’anthropologie structurale « out of America » - Keck, Frédéric (EchoGéo, 2011)
This article analyzes the role of Asia in Lévi-Strauss’s works, and draw conclusions for a structural anthropology of this continent. If Lévi-Strauss seems to devalorize Asia in the literary meditation of Tristes tropiques, he revalorizes it in his scientific writings, seeing it as a continuation of America where phenomena of division and transformation of societies occur with greater length. This link between America and Asia leads Lévi-Strauss to criticize the Durkheimian focalization on Australia and to leave aside the African continent. The last part of the article draws from there hypotheses for an anthropology of Avian flu. Cet article analyse la place de l’Asie dans les textes de Lévi-Strauss et en tire des propositions pour une analyse structurale située sur ce continent. Si Lévi-Strauss semble dévaloriser l’Asie dans la méditation littéraire de Tristes tropiques, il la revalorise dans ses écrits scientifiques, en y voyant un prolongement de l’Amérique où les phénomènes de division et de transformation des sociétés s’effectuent avec une plus grande ampleur. Ce lien entre Amérique et Asie conduit Lévi-Strauss à critiquer la focalisation durkheimienne sur l’Australie et à laisser de côté le continent africain. La dernière partie de l’article en tire des hypothèses pour une anthropologie de la grippe aviaire.